Pencegahan Korupsi di Indonesia dalam Perspektif Hukum Administrasi Negara - Mutia Kardina; Aldri Frinaldi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Corruption is an unethical act, such as embezzlement, accepting bribes, and similar actions. The practice of corruption has permeated all levels of government, including the executive, legislative, and judicial branches, both at the central and local levels. As democracy has developed in Indonesia, the quantity and quality of corrupt activities have also increased. On the other hand, Administrative Law can be described as a guide for government actions, the implementation of activities, the management of public policies, decision analysis, and the tasks of individuals and groups in providing public services and goods. Additionally, Administrative Law is also an academic and theoretical field related to state governance. This research aims to investigate how Administrative Law can play a role in preventing corrupt practices. The results of this study indicate that Administrative Law plays a crucial role in establishing transparent and corruption-free governance. The role of Administrative Law in preventing corruption involves optimizing leadership, improving policy implementation, enhancing the integrity and ethics of the bureaucracy, and increasing public understanding of laws related to corruption.